A Nutrientional composition, functional, and sensory quality of acha-based masa supplemented with groundnut paste - Jerome Adekunle Ayo; Tailem Paul; Zuwaira Abdulhamid Mohammed; Peace Osabo; Mabe Yakubu; Stephen Balkisu (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2025)
Masa, a fermented cereal-based snacks that is becoming popular but relatively low in nutrient contents. This study examined the nutrient composition, functional properties, and sensory quality of acha-based masa supplemented with groundnut paste. Masa flour blends of acha and groundnut paste were prepared in varying ratios (100:0, 95:5, 90:10, 85:15, 80:20) and analyzed using standard laboratory methods at the Central Laboratory of Federal University, Wukari. Results showed that the inclusion of groundnut paste improved the nutritional profile of flour blend masa. The functional properties, physical properties, sensory evaluation, proximate, mineral, and vitamin content were determined. The water absorption decreased from (12.75 to 66.25%), oil absorption decreased from (70.50 to 66.83%), swelling capacity increased from (50.25 to 83.42%), forming capacity increased from (20.50 to 70.50%), the bulk density increased from (0.49 to 0.50%). The taste increased from (3.45 to 3.90%), aroma increased from (4.30 to 4.85%), colour increased from (4.00 to 4.55%), the appearance increased from (4.80 to 5.05%), the texture increases from (4.15 to 5.35%), general acceptability increased from (4.15 to 5.45%). The moisture composition increased from (15.56 to 10.34%), crude protein increased from (11.39 to 12.27%), lipid increased from (2.25 to 2.45%), crude fiber increased from (5.01 to 5.22%), ash content increased from (0.21 to 0.24%). The Fe decreased from (1.94 to 1.81%), the Ca decreased from (3.22 to 2.75%), Mg increased from (0.23 to 0.51%). Vitamin B1 increased from (84.94 to 171.49%), Vitamin B2 increased from (0.00 to 271.82%), Vitamin K increased from (0.28 to 0.93%). Therefore, the sensory evaluation revealed that the taste, aroma, texture, and overall acceptability of masa suggest that groundnut supplemented acha-masa can serve as a functional food to address protein energy malnutrition. However, fortification required to balance the reduction of iron, calcium, and certain vitamins. The sample containing (5%) groundnut paste was the most preferred and acceptable. While the sample without groundnut paste was the poorest.